PENGARUH SUPLEMEN ANTIOKSIDAN TERHADAP KADAR MALONDIALDEHID PLASMA MAHASISWI IPB - Ramatina, Ramatina; Amalia, Leily; Ekayanti, Ikeu (Jurnal Gizi dan Pangan, 2014)
The objective of this study was to analyze the effectiveness of vitamin C, vitamin E and multivitamin-mineral supplements on reducing plasma malondialdehyde (MDA) level among college students of IPB. The design of this study was quasi experimental with pre-post test and control design. The subjects were 24 healthy students and divided into 4 groups, namely 1) vitamin C group (given supplement of vitamin C 500 mg), 2) vitamin E group (given supplement of vitamin E 200 IU), 3) multivitamin-mineral group (given a supplement consisted of vitamin C 500 mg, vitamin E 30 mg, zinc 15 mg and copper 1.5 mg), and 4) control group who were not given any supplement intervention. The supplements in the form of capsule were given once daily for seven days. Before the intervention, the plasma MDA level of subjects were not different significantly (p>0.05). After 7 day intervention, the MDA level of VC, VE, and MVM group were reduced significantly compared to before intervention (p<0.05), whereas plasma MDA level of control group seemed increased although not significant compare to pre-intervention. The largest reduction was occured on vitamin E group (-55.1%), followed by vitamin C group (-47.2%), and multivitamin-mineral group (-44.7%). The ANOVA test shows that there was a significant difference on reduction of plasma MDA levels among groups. The difference occured between control group and each of intervention group of VC, VE, and MVM. There were no significant differences between two groups of intervention (p>0.05). Hence, the study shows that in 7 day intervention, vitamin C, vitamin E or multivitamin-mineral supplement had relative similar effects on reducing plasma MDA level.